Multifunctional Hierarchical Surface Structures by Femtosecond Laser Processing - Kunz, Clemens (Materials (Basel), 2018)
Hierarchical surface structures were fabricated on fused silica by using a fs-laser with a pulse duration τ = 300 fs and a wavelength λ = 512 nm. The resulting surface structures were characterized by scanning electron microscopy, atomic force microscopy and white light interference microscopy. The optical properties were analyzed by transmittance measurements using an integrating sphere and the wettability was evaluated by measuring the water contact angle θ. The silanization of structured fused silica surfaces with trichloro(1H,1H,2H,2H-perfluorooctyl)silane allows to switch the wettability from superhydrophilic (θ = 0°) to superhydrophobic behavior with θ exceeding 150°. It was shown that the structured silica surfaces are a suitable master for negative replica casting and that the hierarchical structures can be transferred to polystyrene. The transmittance of structured fused silica surfaces decreases only slightly when compared to unstructured surfaces, which results in high transparency of the structured samples. Our findings facilitate the fabrication of transparent glass samples with tailored wettability. This might be of particular interest for applications in the fields of optics, microfluidics, and biomaterials.